Violence as social integration in Judas”™ burning in Potrerito and La Cañada - Andrade, Gabriel (Opción, 1970)
This article describes how the use of violence channeled upon a victim can help regenerate social life in a community. Each Easter Sunday, many Venezuelan communities perform ”˜Judas”™burning”™, a ritual in which a puppet representing Judas is symbolically executed. This ritual created a process of collective expiation that propitiates social peace. This article analyzes how these phenomena take place in Potrerito and La Cañada, two villages in Zulia State, Venezuela.